Comprehensive geriatric assessment in patients with hip fracture - Cieza-Macedo, Edwin (2023)
Introduction. Hip fractures are a group of frequent pathologies in frail older adults, with a negative impact on functionality. Objective. To determine the clinical, functional, mental, and social characteristics based on the comprehensive geriatric assessment. Methods. 445 patients were evaluated, comorbidity was measured with the Charlson index, baseline functional state with the Barthel index and the Lawton and Brody scale, mental state with the Pfeiffer questionnaire, delirium using the Confusion Assessment Method and social assessment with the Gijón Socio-Family Scale. Categorical variables were presented as absolute value and percentage and continuous variables as mean and standard deviation. Results. The female sex represented 71.5%, the average age in women was 81.58 years and in men 82.58 years. Visual impairment was 48.8% and hearing impairment 46.1%. 46% had more than one comorbidity. 30.3% were independent for basic activities, as well as 90.3% of women and 64.3% of men were dependent for instrumental activities. Cognitive impairment was present in 53.5% and delirium developed in 20.4%. In the second week, 30.5% were operated and in the third, 21.6%. Mortality was 2.7% during hospitalization. Conclusion. the most frequent characteristics were of an octogenarian, with visual / auditory deterioration, without comorbidity, but multipathological, with slight dependence for basic activities of daily living and cognitive deterioration in a risky social environment.